Evaluation of Head Loss in Drip Irrigation System - Kumar, Sandeep; Singh, Pratap (Journal of Agricultural Engineering, 2008)
The study was conducted to evaluate the head loss in main line and lateral line for drip irrigation system. The study involved four types of emission devices viz. dripper, micro-tube, drip-in and drip tape. The head loss was calculated by measuring loss in pressure head in actual length of main and lateral line at four locations of the system with different spacing and operating pressure head. The minimum and maximum head loss in main and lateral line was for drippers and micro-tubes respectively Emperical equations for head loss combined for all emission devices and individual for each emission device were developed.